2017
DOI: 10.1212/nxi.0000000000000387
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation of thalamic volume differentiates MS from common mimics

Abstract: Objective:To determine whether MRI evaluation of thalamic volume differentiates MS from other disorders that cause MRI white matter abnormalities.Methods:There were 40 study participants: 10 participants with MS without additional comorbidities for white matter abnormalities (MS − c); 10 participants with MS with additional comorbidities for white matter abnormalities (MS + c); 10 participants with migraine, MRI white matter abnormalities, and no additional comorbidities for white matter abnormalities (Mig − c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…In addition to the two VBM analyses presented in the main text, four supplementary VBM analyses were conducted. The first tested volume differences between PwMS and HCs and identified loss of GM volume in PwMS in thalamic areas (which is consistent with findings on MS-induced atrophy) and, to a lesser degree, in MTG (42,43). However, these areas characterized by GM volume loss in PwMS turned out to be of limited importance for relaxationrelated tissue alterations in PwMS because a repetition of the two VBM analyses presented in the main text constrained to the coordinates found in the first supplementary VBM analysis in supplementary VBM analysis 2 did not reveal any significant associations.…”
Section: Figure 3 |supporting
confidence: 73%
“…In addition to the two VBM analyses presented in the main text, four supplementary VBM analyses were conducted. The first tested volume differences between PwMS and HCs and identified loss of GM volume in PwMS in thalamic areas (which is consistent with findings on MS-induced atrophy) and, to a lesser degree, in MTG (42,43). However, these areas characterized by GM volume loss in PwMS turned out to be of limited importance for relaxationrelated tissue alterations in PwMS because a repetition of the two VBM analyses presented in the main text constrained to the coordinates found in the first supplementary VBM analysis in supplementary VBM analysis 2 did not reveal any significant associations.…”
Section: Figure 3 |supporting
confidence: 73%
“…This study investigated the involvement of the cerebello-thalamic tract in the pathogenesis of unilateral MS upper limb tremor. The thalamus was of particular interest as thalamic atrophy had been correlated with worse prognosis in MS patients (Rocca et al 2010 ), is present in the very early stages of MS (Azevedo et al 2015 ; Bergsland et al 2012 ), and has been shown to allow differentiation from other MRI white matter pathologies (Solomon et al 2017 ). We found that contra- and ipsilateral thalamic volumes and ipsilateral SCP area inversely correlated with increased unilateral tremor severity scores.…”
Section: Discussionmentioning
confidence: 99%
“…Also, significant GM volume loss occurred in the right precuneus in relapsing-remitting MS patients with progressive disability ( Hofstetter et al, 2014 ). Moreover, atrophy of specific DGM structures, most notably the thalamus, also occurs in MS patients ( Bishop et al, 2017 ; Houtchens et al, 2007 ; Schoonheim et al, 2015 ; Solomon et al, 2017 ). Atrophy of the thalamus appears to occur especially early and prominently, to be worse in men, and to be associated with cognitive decline ( Schoonheim et al, 2015 ).…”
Section: Challenges Of Pathology Physiology and Treatment Effectsmentioning
confidence: 99%